Cost Modifications during the Early Years of the Use of the National Cardiovascular Data Registry for Quality Improvement (Clinics, 2020)
OBJECTIVES: Quality improvement (QI) initiatives based on data from international registries have been reported previously; however, there is a lack of information on the impact on the costs of medical care associated with the use of these tools. METHODS: Patients admitted due to myocardial infarction (MI), included in the ACTION Registrys and CathPCI Registrys, in a private Brazilian hospital (i.e., the reference hospital) were analyzed. The costs of care of these patients were compared to the costs of MI admissions in nine similar hospitals not included in the same QI program. Regression models were used to analyze the cost change over time between the two groups of hospitals. Readmission rates were compared using logistic regression, adjusting for the same variables as in the cost model. RESULTS: Overall, the annual medical cost inflation in Brazil was higher than the annual cost trend in the reference hospital during the period of analysis. Moreover, the annual in-hospital costs indicate that the reference hospital has a statistically significant 6% lower cost trend for patients with acute MI, compared to patients with the same diagnostic code in the comparison hospitals group, in an adjusted analysis (p-value=0.041). Using multivariable analysis, the readmission rates were also found to be significantly lower in the reference hospital than in the comparison hospitals, with an odds ratio of 0.68 (p-value=0.042). CONCLUSION: The use of the NCDRs as a benchmark to guide QI programs outside the United States was associated with the positive impact of bending the cost curve to below that of national medical inflation and the comparison hospitals’ costs, with a lower incidence of hospital readmission.